Induced systemic resistance against Alternaria sesami, causing blight of sesame and its toxin characterization: Induced systemic resistance against Alternaria sesami, causing blight of sesame and its toxin characterization - A S SAVITHA; M K NAIK; K AJITHKUMAR (Journal of Oilseeds Research, 2023)
Different resistance inducing chemicals were tested for inhibition of growth and induction of resistance against blight in sesame. Among them, salicylic acid (10 mM) was effective in inhibiting the mycelial growth of A. sesami (68.8%) that causes the blight disease of sesame. The resistance inducing chemicals, plant extracts and bioagents tested in vivo, with challenge inoculation of A. sesami, salicylic acid at one per cent concentration was found to be effective in suppressing the pathogen and resulted in higher vigor index (1138.28) followed by P. fluorescens with good germination per cent of 97.35 and vigor index of 1029.85. The higher vigor index obtained in these treatments might be due to their support for increased germination, good root and shoot growth. Further, the pathogen produces toxic metabolite in culture, the crude toxin was extracted and analysed through infra-red analysis, the peak indicated that the compound may contain more than two OH groups and its assay on seeds and seedling of sesame and tomato showed least germination, shoot and root length and necrotic symptoms respectively.